Clinical applications of BioAggregate in pediatric dentistry: Case reports - Caliskan Secil; Tuloglu Nuray; Bayrak Sule (Srpski Arhiv za Celokupno Lekarstvo, 2019)
Introduction. Calcium-silicate-based, nanoparticle-sized BioAggregate is produced as an alternative version of mineral trioxide aggregate (MTA). It contains additives such as calcium phosphate and silicon dioxide but does not contain aluminium oxide and bismuth oxide. Studies have shown that BioAggregate’s calcium-ion release is better than these qualities in MTA concerning fracture and acid resistance, biocompatibility and sealing ability. Case outline. In this paper, we examine eight case reports. These reports describe the long-term results of using BioAggregate in areas such as pulpotomy and root canal treatment in primary and permanent teeth, partial pulpotomy, artificial apical barrier construction of permanent teeth, root resorption repair, and treatment of dens in dente. Conclusion. As evidenced by the case reports examined here, BioAggregate can be used as alternative material to MTA in many dental treatments. These reports also show that the biocompatibility, antibacterial properties, hardening when moisture is present, ideal expansion percentage, impermeability, and dentine adhesion features of BioAggregate provide advantages in clinical use.